A disciplina de educação física no contexto da reforma curricular da secretaria da educação do estado de São Paulo - Lopes, Franz Carlos Oliveira (2012)
The educational policy studies, specially concerning to curricular issues, have been taking a significant time of the educational debate. From this perspective, public educational policy, curriculum and student formation issues worry us since the curriculum is the guidance in the formation process. Consequently, the present research object of study is the Physical Education Curricular Proposal elaborated by the Secretary of Education of São Paulo State (SEE-SP) in the context of São Paulo faz escolar Program. Pursuing to comprehend the foundations and guidelines of this proposal we investigated those documents elaborates by the Secretary. Data revealed that the general reform guidelines and particularly the ones of Physical Education discipline are founded on the pedagogy of competence formation. Therefore, even considering the announcement of critical and cultural formation speech, that possibility is limited due to the utilitarian and adaptive orientation, characteristic of that pedagogy.